1999
DOI: 10.1046/j.1439-0450.1999.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Activity of the Purified Protein Antigen of Erysipelothrix rhusiopathiae in Pigs

Abstract: We purified the protein antigen (P64), which contains 66 and 64 kDa proteins, from the alkaline extract (AE) of whole cells of Erysipelothrix rhusiopathiae strain Agata (serovar 5) to determine the protective activity of the antigen against E. rhusiopathiae infection in pigs. The serum titre of antibody against P64 rapidly increased in pigs immunized with 500 and 100 mg of P64 and reached maximum values at 3 weeks after the first immunization (1 week after the second immunization). However, the serum antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Briefly, whole-cell proteins from either the ∆spaA mutant or the wild-type strain C43065 were compared by SDS-PAGE, followed by Coomassie staining and western blotting. Although several nonspecific proteins (14,20,28, and 66 kDa protein bands) were evident in both samples by Coomassie staining, the 64 kDa protein only appeared in samples of the wild-type strain, but not in samples of the mutant strain (Fig. 3C).…”
Section: Confirmation Of Spaa Deletion Mutant By Rt-pcr and Western B...mentioning
confidence: 94%
See 1 more Smart Citation
“…Briefly, whole-cell proteins from either the ∆spaA mutant or the wild-type strain C43065 were compared by SDS-PAGE, followed by Coomassie staining and western blotting. Although several nonspecific proteins (14,20,28, and 66 kDa protein bands) were evident in both samples by Coomassie staining, the 64 kDa protein only appeared in samples of the wild-type strain, but not in samples of the mutant strain (Fig. 3C).…”
Section: Confirmation Of Spaa Deletion Mutant By Rt-pcr and Western B...mentioning
confidence: 94%
“…Surface protective antigens of gram-positive bacteria have been implicated in both virulence and protection during bacterial infection [10,27]. Among several cell surface proteins identified in E. rhusiopathiae, SpaA has been shown to be a 64 kDa surface protective antigen associated with the induction of highly protective antibodies against E. rhusiopathiae after infection in both mice and pigs [5,14,17,28]. Structural and sequence analyses have revealed that the C-terminal region of SpaA is very similar to the choline-binding proteins of Streptococcus pneumoniae, which can bind to choline residues of teichoic acid [8].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical signs of SE can be divided into three types: acute (septicemia), subacute (urticaria) and chronic (arthritis, lymphadenitis and endocarditis) [ 20 ]. Surface protective antigen (Spa) A is well known as one of the major protective antigens of E. rhusiopathiae [ 7 , 21 ]. The N-terminal half of the hypervariable region of SpaA in particular has been shown to be important for specific immunity to the infection [ 3 , 13 , 17 ].…”
mentioning
confidence: 99%